The Effect of Third-Party Funds, Deposit Interest Rates, and Financial Literacy on Financial Performance at Bank BJB - Supriadi, Deni; Rinaldo, Dito (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the effect of Third-Party Funds (DPK) and deposit interest rates on the financial performance of Bank BJB, with financial literacy as an intervening variable. The background of this research is based on the phenomenon that increases in DPK and competitive deposit interest rate strategies do not always lead to optimal financial performance. This indicates the importance of internal factors, particularly the financial literacy of management and front-line employees, in managing funds, assessing risks, and making effective financial decisions. This research employs a quantitative approach using multiple regression analysis and mediation testing. The analysis is conducted through several stages, including descriptive statistical analysis, classical assumption tests, two-stage regression analysis, and significance testing (t-test, F-test, and coefficient of determination). The mediation effect is examined using the Sobel test and/or bootstrapping methods. The results are expected to show that DPK and deposit interest rates have both direct and indirect effects on financial performance through financial literacy. Financial literacy acts as an intervening variable that strengthens the relationship between external factors and financial performance by improving fund management effectiveness, risk control, and decision-making quality. This research contributes theoretically to the development of financial literacy literature in the banking sector and provides practical implications for Bank BJB management in enhancing financial performance through strengthening internal capabilities.